Use of progestagens to preserve pregnancy: modern approaches - S.I. Zhuk; I.V. Us (Publishing House TRILIST, 2023)
Review objectives: to summarize current and clinical data on the role of progesterone support in women at risk of miscarriage and premature pregnancy according to the standards of evidence-based medicine. Control of plasma progesterone levels is a fundamental tool for managing the effectiveness of assisted reproductive technologies. The association of a low level of serum progesterone with lower rates of current pregnancy and live birth in cycles of assisted reproductive technologies was revealed. Patients with low serum progesterone on the day of embryo transfer need individualized support of the luteal phase, which involves adding additional doses of progesterone to standard regimens. Vaginal micronized progesterone is currently believed to be the only progestogen that increases the likelihood of a live birth in women with bleeding in early pregnancy which has one or more miscarriages. Vaginal progesterone can be considered for patients with a high risk of miscarriage in the following modes: with vaginal bleeding and a history of one or more miscarriages (threatened miscarriage) - 400 mg twice a day, starting with the detection of vaginal bleeding up to 16 full weeks of pregnancy; with a history of three or more pregnancy losses of unknown etiology (habitual miscarriage) - asymptomatic patients вЂ" 200 mg twice a day up to 12 full weeks of pregnancy; patients with vaginal bleeding - 400 mg 2 times a day up to 16 weeks of pregnancy. Currently, there is no evidence of the effectiveness other forms of progesterone and other doses. Conclusions. Vaginal micronized progesterone demonstrated: high efficiency as a standard of luteal phase support; increasing the chance of a live birth in women with a double risk factor for miscarriage (vaginal bleeding in the 1st trimester and в‰Ґ1 previous miscarriage); the absence of safety problems for the fetus and the health of newborns when used in the early and late stages of pregnancy.